Identification of areas with soil loss above the tolerable using NDVI for calculating the C factor of USLE - Da Cunha E Silva, Darllan Collins [UNESP]; Filho, José Luiz Albuquerque; Sales, Jomil Costa Abreu [UNESP]; Lourenço, Roberto Wagner [UNESP] (Universidade Federal do Paraná, 2017)
One of the main problems related to the conservation of the watershed soils is the hydric erosion of the soil, leading to particles transportation to water bodies as consequence, especially in those regions with agricultural activities. Therefore, this study main purpose was to demonstrate the factor c calculation methodology application, through the Normalized Difference Vegetation Index (NDVI) using geoprocessing techniques and mathematical modeling to quantify the soil loss in the Una River Basin, through the Universal Soil Loss Equation (USLE), it was possible to evaluate the different soil losses found according to thedifferent land uses and occupations. The results showed a low soil loss potential, which is a result of the association of different factors, in special, vegetation cover. wnicn corresponds to 41% the watersnea area, ana was aiso responsiDie Tor maintaining erosion rates lower tnan 10 t.ha-l.year-1 in 93, 4% from the study area, while erosion rates higher than 10 t ha-l.year-1 werelocated within areas with agricultural activities and high steepness. The applied methods have proven to be efficient and highly contribute to river basins studies regarding the planning, management and soil conservation.
Identificaçào de áreas com perda de solo acima do tolerável usando NDVI para o cálculo do fator C da USLE
Keywords: Erosion; Geoprocessing; USLE; Watershed